Developing and leveraging digital twins in engineering design - Anwer, Nabil; Stark, Rainer; Tao, F.; Erkoyuncu, John Ahmet (Elsevier, 2025)
Digital twins are digital representations of real-world entities constantly fed by dynamic, bidirectional communication and updates throughout the lifecycle of these sophisticated paired systems. Developing digital twins in production engineering creates new avenues for engineering design in the context of digital transformation in manufacturing and sociotechnical systems. This paper reviews the foundational concepts, methodologies, and applications of digital twins in engineering design, covering both their architecture and development (engineering of digital twins), and their utilisation to enhance design activities (engineering with digital twins). An overview of the current state-of-the-art is presented, challenges are highlighted, and future research directions are addressed.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; 9 Industry, Innovation and Infrastructure; Industrial Engineering & Automation; 4014 Manufacturing engineering; 4017 Mechanical engineering; Design; Digital twin; Digital twin engineering